Part A: Application of fluorescent markers onto CRISPR-associated proteins/ Part B: Substitution of cysteine residues in CRISPR associated Protein Cas1 - Parr, Lochlan (2024)
Part A: Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems mediate prokaryotic adaptive immunity against mobile genetic elements (MGEs), where MGE sequences are captured and stored as spacers in CRISPR loci. CRISPR-associated (Cas) proteins Cas1 and Cas2 form a complex that integrates these spacers into CRISPR arrays, generating adaptive immunity through CRISPR interference. While the mechanisms of the Cas1-Cas2 complex are understood, less is known about its regulatory pathways, particularly because it has been shown to interact with proteins far outside its genetic locality, sometimes from different chromosomes. Fluorescent proteins (FPs) have successfully been used to tag proteins for over a century, enhancing our understanding of their intermolecular interactions. Site directed mutagenesis (SDM) can be used to substitute all Cas1 cysteine residues for alternative inert amino acids, and implementation of another cysteine at a more accessible site would allow the binding of fluorescent maleimide proteins, accommodating advanced microscopy techniques to investigate molecular interactions in vivo, thereby improving our understanding of Cas1 regulatory interactions. The methods to produce the target mutant Cas1 protein are discussed in this review, including techniques such as Sanger sequencing, pilot protein overexpression and spacer acquisition assays, which are used to verify the quality and viability of the product.